DEKONTRUKSI KAFA’AH BAGI WANITA PESANTREN DAN NON PESANTREN (Fenomena Memilih Pasangan Pada Masyarakat Desa Karanganyar Kec. Ambulu) - Luluk Fitriyati (Mabahits : Jurnal Hukum Keluarga Islam, 2022)
Kafa'ah is an Islamic concept in choosing a good and appropriate partner, but it does not mention in detail the efforts to get a good partner in Islam. The Karanganyar Village community is an example of a community that makes kafa'ah a consideration in choosing a life partner. In this study, there are two groups that will be research subjects, namely women who graduate from Islamic boarding schools and women who do not graduate from Islamic boarding schools. By using a qualitative approach (Field Research) and the type of phenomenological research. This study resulted: (1) kafa'ah women in pesantren prioritize religious understanding and other factors are only complementary, while non-pesantren women prioritize higher education and establishment. (2) the application of kafa'ah for women in Islamic boarding schools is religion, obedience and attention to parents. While the application of non-pesantren women are: faithful, responsible and knowing the limits of the opposite sex.